Charniodiscus and Arborea Are Separate Genera Within the Arboreomorpha: Using the Holotype of C. concentricus to Resolve a Taphonomic/Taxonomic Tangle - Pérez-Pinedo, Daniel; McKean, Christopher; Taylor, Rod; Nicholls, Robert; McIlroy, Duncan (Frontiers in Earth Science, 2022)
Charniodiscus is one of the most iconic and first described of the Ediacaran frondose taxa. Since the diagnosis of the holotype of C. concentricus in 1958, the scarcity and poor preservation of unequivocal specimens has resulted in genus-level taxonomic uncertainty. Since the recent reinterpretation of C. concentricus as a multifoliate frond, other Charniodiscus species—all of which are bifoliate—have been left in taxonomic limbo, with most authors comparing them to the clade Arboreomorpha and also the Rangeomorpha. Reconsideration of the taphonomy of the holotype of C. concentricus has revealed that the frond is bifoliate as first described, and also that the frondose portion was broadly conical rather than planar as previously inferred. The conical frond of Charniodiscus is thus morphologically quite different from all other frondose taxa within the Arboreomorpha. Our emendation of the generic diagnosis of Charniodiscus to encompass bifoliate arboreomorphs with conical fronds without a backing sheet distinguishes Charniodiscus from more planar leaf-like arboreomorphs such as Arborea, which has a distinctive backing sheet. Additionally, we find no evidence of rangeomorph-type fractal branching in Charniodiscus.